WHY JOURNALISTS LIE: THE TROUBLESOME TIMES FOR JANET COOKE, STEPHEN GLASS, JAYSON BLAIR, AND BRIAN WILLIAMS. - SPURLOCK, JEFFERSON (ETC: A Review of General Semantics, 2016)
The article offers information on several American journalists including Janet Cooke, Jayson Blair, and Stephen Glass. Topics mentioned include the reasons why some journalists tend to lie, the credibility of journalists in giving factual information, and the dismissal of Cooke, Blair, and Glass for creating and giving false news.